Catalytic decarboxylation of crude oil in a fixed-bed pyrolysis reactor - Festus M. Adebiyi; Odunayo T. Ore; Praise B. Oyegoke (Discover Energy)
Abstract This study focused on using titanium dioxide (TiO2) as a catalyst to decarboxylate crude oil from the Imo oil field in Nigeria. The TiO2 catalyst was characterised using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis (TGA). XRD investigation identified rutile-TiO2 as the primary crystalline phase, with important diffraction peaks matching the ASTM standard for rutile. SEM showed extensive agglomerations of TiO2 particles, whereas FT-IR detected surface functional groups such as hydroxyl, carbonyl, and aromatic. TGA identified three separate weight-loss stages, the biggest of which occurred in the devolatilization region, accounting for around 84%. The catalytic decarboxylation process revealed a considerable decrease in the total acid number (TAN) of the crude oil as the temperature increased, reaching a TAN of 0.28 mg KOH g⁻1 at 300 °C, with 96.35% decarboxylation. The TiO2-catalyzed process outperformed thermal cracking alone, resulting in less oxygenated functional groups and increased oil quality. These findings show that rutile-TiO2 can be an excellent catalyst for decarboxylation in crude oil refining.